(untitled) (International Journal of Engineering and Computer Science, 2014)
The advances in computer and information technology together with the rapid evolution of multimedia data are resulted in the huge growth of the digital video. Due to the rapid growth of digital data and video database over the Internet, it is becoming very important to extract useful information from visual data. The scientific community has increased the amount of research into new technologies, with a view to improve the digital video utilization: its archiving, indexing, accessibility, acquisition, store and even its process and usability. All these parts of the video utilization entail the necessity of the extraction of all important information of a video, especially in cases of lack of metadata information. This paper describes importance of descriptive metadata of video, categorization of video contents based on video descriptive metadata, and high level metadata based web video modeling. The main goal of this paper is to construct high level descriptive metadata with and without timeline for all the category of videos and extraction of metadata from web videos such as YouTube and Face Book. By using the high level descriptive metadata information, a user is facilitated on the one hand to locate a specific video and on the other hand is able to comprehend rapidly the basic points and generally, the main concept of a video without the need to watch the whole of it.